Non-Native Arabic Learners’ Social Media Usage and Motivation Influencing Learning of Arabic Language in Malaysian Public Universities - Di, Xuan; Ismail, Wail Muin; Zailani, Muhammad Azhar (International Journal of Language Education, 2020)
This paper aims to clarify the concepts related to the use of social media usage and motivation and their effect on the learning of a new language. They have also investigated the relationship between these variables and determined the influence of motivation and SMU on the academic performance of the students. For this purpose, quantitative survey was employed by distributed questionnaires which adopted from Monachesi et al. (2008) data language technologies for lifelong learning along with the Motivated Strategies for Learning Questionnaires (MSLQ) amongst 317 Arabic learners to six selected universities. They carried out quantitative data analysis by using SPSS and SmartPLS. The finding reported that these learners SMU displayed a significant correlation with motivation. A variation in the results was noted according to the year of study for all the learners. Furthermore, the results indicated that self-efficacy showed a varying effect on the academic performance of the students. The researchers discussed the results related to the learning of a language and the educational practices which were implemented. The results of this study could benefit the instructors, faculty and the student population